Three-dimensional extent of flow stagnation in transcatheter heart valves. Issue 154 (22nd May 2019) - Raghav, Vrishank; Clifford, Chris; Midha, Prem; Okafor, Ikechukwu; Thurow, Brian; Yoganathan, Ajit
Abstract : The recent unexpected discovery of thrombosis in transcatheter heart valves (THVs) has led to increased concerns of long-term valve durability. Based on the clinical evidence combined with Virchow's triad, the primary hypothesis is that low-velocity blood flow around the valve could be a primary cause for thrombosis. However, due to limited optical access in such unsteady three-dimensional biomedical flows, measurements are challenging. In this study, for the first time, we employ a novel single camera volumetric velocimetry technique to investigate unsteady three-dimensional cardiovascular flows. Validation of the novel volumetric velocimetry technique with standard planar particle image velocimetry (PIV) technique demonstrated the feasibility of adopting this new technique to investigate biomedical flows. This technique was used to quantify the three-dimensional velocity field in the vicinity of a validated, custom developed, transparent THV in a bench-top pulsatile flow loop. Large volumetric regions of flow stagnation were observed in the neo-sinus throughout the cardiac cycle, with stagnation defined as a velocity magnitude lower than 0.05 m s −1 . The volumetric scalar viscous shear stress quantified via the three-dimensional shear stress tensor was within the range of low shear-inducing thrombosis observed in the literature. Such high-fidelity volumetric quantitative data and novel imaging techniques used to obtain it will enable fundamental investigation of heart valve thrombosis in addition to providing a reliable and robust database for validation of computational tools.